2022
DOI: 10.1007/s41061-022-00400-x
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Metal Complexes as Emerging Tools for Lipid Imaging

Abstract: Fluorescence microscopy is a key tool in the biological sciences, which finds use as a routine laboratory technique (e.g., epifluorescence microscope) or more advanced confocal, two-photon, and super-resolution applications. Through continued developments in microscopy, and other analytical methods, the importance of lipids as constituents of subcellular organelles, signalling or regulating molecules continues to emerge. The increasing recognition of the importance of lipids to fundamental cell biology (in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…281,282 In addition, based on the advantages of NIR luminescence, many NIR metal agents have been devised to facilitate cell imaging in order to expose many biological processes. 283 Peng et al reported a novel Ru–I complex containing cyanine fluorophores. 147 Ru-1 is positively charged, easily soluble in water, can be quickly absorbed by cancer cells, and emits green light.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…281,282 In addition, based on the advantages of NIR luminescence, many NIR metal agents have been devised to facilitate cell imaging in order to expose many biological processes. 283 Peng et al reported a novel Ru–I complex containing cyanine fluorophores. 147 Ru-1 is positively charged, easily soluble in water, can be quickly absorbed by cancer cells, and emits green light.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“… 8 However, these examinations of lipids hinge on biopsy invasion or external labeling, which demands complex sample preparation procedures and might incur toxicity or changes in metabolic conditions 7 10 Hence, a label-free and noninvasive imaging modality is desired for biomedical lipid studies, which eliminates biosafety concerns and allows easy implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Various LD-specific fluorescent probes have been developed, including commercially available ones. These probes provide a useful means to assess the progression of NAFLD by observing changes in the number and size of LDs in hepatic tissues in vivo and ex vivo . However, it is usually difficult to quantitatively evaluate oxygen levels in hepatic tissues in NAFLD using these fluorescent LD probes. To image LDs in the hepatic tissues of NAFLD and quantitatively assess their oxygen levels simultaneously, it is essential to develop oxygen probes with high cellular uptake efficiency and specific localization to LDs.…”
Section: Introductionmentioning
confidence: 99%